The Effect Of Incentives And Work Discipline On Employee Performance At Pt Adhiguna Putera Padang Branch - May Yohandra Fikra; Febsri Susanti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Optimal employee performance is needed to achieve the goals of a company. This study aims to determine the effect of incentives on employee performance and the effect of work discipline on employee performance at PT Adhiguna Putera Padang Branch, sampling method using total sampling technique, where the entire population was sampled, as many as 46 people. Hypothesis testing in this study uses multiple linear regression to determine the extent of incentives and work Discipline on employee performance. The results of this study indicate that: Incentives have a positive and significant effect on employee performance, and work discipline has a positive and significant effect on employee performance.